2023
DOI: 10.1002/jeq2.20493
|View full text |Cite
|
Sign up to set email alerts
|

Machine‐learning model to delineate sub‐surface agricultural drainage from satellite imagery

Fleford S. Redoloza,
Tanja N. Williamson,
Alexander O. Headman
et al.

Abstract: Knowing subsurface drainage (tile‐drain) extent is integral to understanding how landscapes respond to precipitation events and subsequent days of drying, as well as how soil characteristics and land management influence stream response. Consequently, a time series of tile‐drain extent would inform one aspect of land management that complicates our ability to explain streamflow and water‐quality as a function of climate variability or conservation management. We trained a UNet machine‐learning model, a convolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Thus, these methods were used for evaluation of the optimal combination of geospatial data used for separating different land cover classes [45,46]. These and other results reported in previous studies also indicated that the use of Python improves the performance of the classification and attains the required automation and accuracy level in the process of image classification [47][48][49]. Nevertheless, improvements and flexibility are achieved in the Geographic Resources Analysis Support System (GRASS) GIS software, which presents a smart combination of the existing Python libraries with cartographic toolsets and a powerful image processing functionality.…”
Section: Related Workmentioning
confidence: 55%
“…Thus, these methods were used for evaluation of the optimal combination of geospatial data used for separating different land cover classes [45,46]. These and other results reported in previous studies also indicated that the use of Python improves the performance of the classification and attains the required automation and accuracy level in the process of image classification [47][48][49]. Nevertheless, improvements and flexibility are achieved in the Geographic Resources Analysis Support System (GRASS) GIS software, which presents a smart combination of the existing Python libraries with cartographic toolsets and a powerful image processing functionality.…”
Section: Related Workmentioning
confidence: 55%